До питання імплементації зарубіжного досвіду забезпечення територіальної оборони в українські правові реалії - Мартинюк, А. В.; Martyniuk, A. V. (Європейські перспективи. - 2024. - № 1. - С. 225-230, 2024)
У статті, спираючись на аналіз наукових поглядів вчених відмічено, що провідні західні держави, які посідають лідируючі світові позиції в економічній та політичній площині, характеризуються високим рівнем правової і соціальної захищеності їх громадян, досить багато уваги приділяють питанням територіальної оборони, забезпечення якої у них розглядається як невід’ємна складова національної безпеки. Опрацьовано можливості використання такого досвіду в українських реаліях.

It has been established that the leading Western states, which occupy leading positions in the world in the economic and political plane, are characterized by a high level of legal and social protection of their citizens, pay a lot of attention to issues of territorial defense, the provision of which is considered an integral component of national security. However, in recent years, the interest of both the public authorities and the society of these countries in the issue of ensuring territorial defense has increased significantly, which is due to the threats and challenges that have appeared both to individual states and the world community in recent years, in particular: the pandemic of the coronavirus disease; growing tension in relations between the United States and China; Russia’s full-scale military invasion of Ukraine and the aggressor’s occupation of part of our country’s territory; military conflict in the Middle East; military coups in African countries, etc. The following important aspects of the implementation of this provision, which are useful for consideration and implementation in the conditions of Ukrainian realities, are highlighted, namely: active involvement of the population, in particular youth, in territorial defense through meaningful and purposeful educational work; creation of a network of territorial defense forces training centers, while special attention should be paid to the selection of candidates for training officers and commanders; the formation of special units in the territorial defense forces, focused on the performance of specific tasks and functions (for example, control of unmanned aerial vehicles); systematic involvement of law enforcement agencies, including military formations with law enforcement functions, in the implementation of territorial defense measures, as well as participation in the training of personnel and reserves for territorial defense forces.

В статье, опираясь на анализ научных взглядов ученых, отмечено, что ведущие западные государства, занимающие лидирующие мировые позиции в экономической и политической плоскости, характеризуются высоким уровнем правовой и социальной защищенности их граждан, достаточно много внимания уделяют вопросам территориальной обороны, обеспечение которой у них рассматривается как неотъемлемая составляющая национальной безопасности. Проработаны возможности использования такого опыта в украинских реалиях.
Keywords: зарубіжний досвід; foreign experience; зарубежный опыт; територіальна оборона; territorial defense; территориальная оборона; забезпечення територіальної оборони; provision of territorial defense; обеспечение территориальной обороны; національна безпека; national security; национальная безопасность